ANALISIS PARSON PRODUCT MOMENT DAN ALPHA CRONBACH DALAM PENGEMBANGAN NEED ASSESMENT BIMBINGAN DAN KONSELING - Fadkhurosi, Adnan (Universitas Muria Kudus, 2023)
This study aims to produce a product in the form of an assessment instrument for the students' needs in order to determine the Guidance and Counseling program at SMA Negeri 1 Sumberlawang. This instrument was developed through the ADDIE model research development method. The instrument for assessing that needs of students at SMA Negeri 1 Sumberlawang is an adoption of existing instruments, and is retested through validity and reliability tests with different subjects and the latest time. Sample that involved in this research and development amounted to 84 students, from a population of 101 students. Based on the validity and reliability test, shows that instrument meet the requirements in terms of validity and reliability. Referring to the description above, student needs assessment instrument is suitable for use in order to collect information on the needs of participants, so that a concrete Guidance and Counseling program can be prepared based on the needs of students.